Preparation method and application of sludge dry powder based filling material capable of purifying gas

A sludge dry powder-based filling material is prepared by mixing and sintering with additives to address the challenges of sludge ash disposal, achieving efficient CO2 and H2S removal and mechanical strength, thereby enhancing resource utilization and reducing costs.

CN119191817AInactive Publication Date: 2024-12-27SOUTHWEST PETROLEUM UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411714153.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The treatment and resource utilization of sludge incineration ash, particularly the high cost of removing harmful substances and increasing its value, pose challenges in existing methods, especially in the context of sludge dry powder disposal.

Method used

A method involving mixing sludge dry powder with metal salts, alkali, solvent, lime, steel slag, lithium slag, cement, and fiber, followed by granulation and sintering, to create a filling material that can purify gas by absorbing CO2 and H2S and provide mechanical strength.

Benefits of technology

The method enhances the resource utilization of sludge dry powder, reduces treatment costs, improves environmental quality, and increases economic benefits by effectively removing CO2 and H2S, while maintaining mechanical strength and preventing microbial reproduction in oil and gas wells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191817A_ABST
    Figure CN119191817A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of air purification material preparation, in particular to a preparation method and application of a sludge dry powder based filling material capable of purifying gas, and the preparation method comprises the following steps: A, uniformly mixing sludge dry powder, metal salt, alkali and a solvent to form a solution, stirring for reaction, and drying to obtain modified sludge dry powder; b, uniformly mixing the sludge dry powder modified in the step A, lime, steel slag, lithium slag, cement, fiber and water to obtain a mixture, and granulating, sintering and naturally curing the mixture to finally obtain the filling material.According to the material, underground carbon dioxide and hydrogen sulfide are removed, desulfurization and decarburization processes are reduced, and economical efficiency is improved; and carbon dioxide and hydrogen sulfide generated by microorganism breeding are avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of air purification material preparation, and in particular to a preparation method and application of a sludge dry powder-based filling material capable of purifying gas. Background Art

[0002] With the acceleration of urbanization, the amount of sludge generated by sewage treatment plants is increasing. Sludge incineration is widely used around the world as an effective method to reduce sludge volume and kill pathogens. However, the sludge after incineration will form dry powder (incineration ash or fly ash), and its treatment and utilization have become urgent problems to be solved.

[0003] At present, the main treatment methods for dry powder from sludge incineration include resource utilization and safe landfill. Resource utilization mainly includes use as building materials, soil conditioners and industrial raw materials. In some countries and regions, a relatively mature dry powder recycling system has been established, such as adding dry powder to concrete to improve its performance, or using dry powder for road construction. In addition, some dry powder can be put back into the incineration process as auxiliary fuel. For dry powder that is difficult to utilize as a resource, it is disposed of by safe landfill. Although certain progress has been made in the treatment and utilization of dry powder from sludge incineration, it still faces many challenges, especially the relatively high cost of dry powder treatment, especially the large investment required to remove harmful substances and increase the value of resource utilization. Summary of the invention

[0004] In order to solve the above technical problems, an embodiment of the present invention provides a preparation method and application of a sludge dry powder-based filling material capable of purifying gas.

[0005] To achieve the above object, the embodiments of the present invention adopt the following technical solutions: In one aspect, the present invention provides a method for preparing a sludge dry powder-based filling material capable of purifying gas, comprising the following steps: A. Mix sludge dry powder, metal salt, alkali and solvent into a solution, stir to react and dry to obtain modified sludge dry powder; the sludge dry powder contains 35~40wt% SiO2, 10~20wt% Al2O3, 5~10wt% Fe2O3, 10~20wt% CaO, MgO, Na2O, K2O each accounting for 1~5wt% and a small amount of Zn, Cu, Pb, Cr and other metals and salts.

[0006] B. Evenly mix the sludge dry powder modified in step A, lime, steel slag, lithium slag, cement, fiber and water to obtain a mixture, granulate, sinter and naturally cure the mixture to finally obtain a filling material.

[0007] In some embodiments, in step A, the solid content of the solution is 30-50 wt %.

[0008] In some embodiments, in step A, the mass ratio of the sludge dry powder, the metal salt and the alkali is 8:1:1.

[0009] In some embodiments, in step A, the metal salt comprises at least two of iron nitrate, magnesium nitrate, aluminum nitrate, nickel nitrate, cerium nitrate, copper nitrate, zinc nitrate, manganese nitrate and cobalt nitrate.

[0010] In some embodiments, in step A, the base is sodium hydroxide or urea.

[0011] In some embodiments, in step A, the solvent comprises at least one of water, ethanol, propanol, ethylene glycol, propylene glycol and butylene glycol.

[0012] In some embodiments, in step A, the stirring reaction temperature is 80-150°C, the time is 2-24 h, and the drying temperature is 50-150°C.

[0013] In some embodiments, in step B, the mass ratio of the sludge dry powder, lime, steel slag, lithium slag, cement and fiber is (20-30): (5-10): (30-40): (10-20): (3-10): (1-5), and the water content of the mixture is 5-10wt%.

[0014] In some embodiments, in step B, the fiber includes at least one of bamboo charcoal fiber, basalt fiber, polyacrylamide fiber, carbon fiber and gypsum fiber; In step B, the sintering is a three-stage sintering, the first stage is kept at 100-200°C for 1-10 h, the second stage is kept at 400-600°C for 1-10 h, and the third stage is kept at 900-1100°C for 1-10 h.

[0015] On the other hand, the present invention also provides an application of the filling material prepared by the above-mentioned preparation method in desulfurization and decarbonization in oil and gas wells.

[0016] The present invention uses sludge dry powder as the raw material of underground filling material, which can realize the recycling of resources and conform to the concept of circular economy and sustainable development. It not only reduces the direct landfill or incineration of sludge dry powder, reduces the pollution to land and air, helps to improve the environmental quality, but also reduces the production cost of filling materials and improves the economic benefits of enterprises. By adding sludge dry powder, the pore structure of the filling material can be improved and unique functions can be given to it, while not affecting its mechanical strength.

[0017] The present invention focuses on the resource utilization of sludge dry powder and proposes an oil and gas well filling material that can remove carbon dioxide and hydrogen sulfide by making sludge dry powder. The resource utilization of sludge dry powder is realized, the cost of sludge dry powder treatment is reduced and its economic value is improved, while the desulfurization and decarbonization process in the oil and gas field exploitation process is reduced, and the economic benefits are improved.

[0018] Compared with the prior art, the present invention has at least the following beneficial effects: Metal salts form metal oxide materials with 500 m 2 / g or more specific surface area, can absorb carbon dioxide and hydrogen sulfide. In addition, sulfate-reducing bacteria (producing hydrogen sulfide) and iron bacteria in the well can form strong oxidizing groups through the catalytic oxidation of the material of the present invention to achieve sterilization function, avoiding the reproduction of microorganisms in the well to produce carbon dioxide and hydrogen sulfide and corrosion of the well wall. CaO in lime, steel slag and lithium slag can absorb CO2 to form CaCO3, fix carbon dioxide, and other metal oxides in steel slag and lithium slag can also absorb or adsorb carbon dioxide, and can be used as a skeleton material to provide mechanical strength. Fibers can enhance the mechanical strength of filling materials. The present invention can realize the resource utilization of dry powder after sludge incineration treatment, reduce the process flow, reduce the treatment cost, and improve the economic value of sludge; the material of the present invention can remove carbon dioxide and hydrogen sulfide in the well, reduce the desulfurization and decarbonization process, and improve the economy; sterilization and antibacterial in the well, avoiding the reproduction of microorganisms to produce carbon dioxide and hydrogen sulfide. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the SEM image of the modified sludge dry powder in Example 2; Figure 2 This is the TEM image of the modified sludge dry powder in Example 2; Figure 3 This is a graph showing the removal rates of carbon dioxide and hydrogen sulfide in Example 2. DETAILED DESCRIPTION

[0020] The following will be combined with the accompanying drawings to clearly and completely describe the technical solutions in some embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, rather than all the embodiments. Based on the embodiments provided by the present disclosure, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present disclosure.

[0021] Example 1

[0022] S1. Dissolve sludge dry powder, metal salt and sodium hydroxide in water to obtain a solution with a solid content of 35wt%, mix and stir evenly, react at 80°C for 4 h, and then dry at 70°C to obtain modified sludge dry powder, wherein the mass ratio of sludge dry powder: metal salt: sodium hydroxide is 8:1:1, and the metal salt is magnesium nitrate and aluminum nitrate in a mass ratio of 2:1; S2, mixing the modified sludge dry powder, lime, steel slag, lithium slag, cement and basalt fiber in a mass ratio of 25:7:33:18:8:3, adding water to obtain a uniformly mixed slurry with a water content of 8wt%, and then granulating it with a granulator; S3. The granules obtained after granulation are first kept at 150°C for 2 h, then at 450°C for 3 h, then at 1000°C for 1 h, and finally naturally cured.

[0023] Example 2

[0024] S1. Dissolve sludge dry powder, metal salt and urea in ethylene glycol to obtain a solution with a solid content of 40wt%, mix and stir evenly, react at 120°C for 6h, and then dry at 70°C to obtain modified sludge dry powder, wherein the mass ratio of sludge dry powder: metal salt: urea is 8:1:1, and the metal salt is nickel nitrate and iron nitrate in a mass ratio of 3:1; S2, mixing the modified sludge dry powder, lime, steel slag, lithium slag, cement and gypsum fiber in a mass ratio of 24:6:32:15:8:2, adding water to obtain a uniformly mixed slurry with a water content of 10wt%, and then granulating it with a granulator; S3. The granules obtained after granulation are first kept at 170°C for 1.5 h, then at 500°C for 2 h, then at 950°C for 1.5 h, and finally naturally cured.

[0025] from Figure 1 and Figure 2 It can be seen that the modified sludge dry powder has a porous structure, which is conducive to the adsorption of carbon dioxide and hydrogen sulfide. Figure 3 It can be seen that the filling material has excellent removal ability for carbon dioxide and hydrogen sulfide.

[0026] Example 3

[0027] S1. Dissolve sludge dry powder, metal salt and urea in propylene glycol to obtain a solution with a solid content of 45wt%, mix and stir evenly, react at 160°C for 2 h, and then dry at 70°C to obtain modified sludge dry powder, wherein the mass ratio of sludge dry powder: metal salt: urea is 8:1:1, and the metal salt is copper nitrate and cerium nitrate in a mass ratio of 3:2; S2, mixing the modified sludge dry powder, lime, steel slag, lithium slag, cement and basalt fiber in a mass ratio of 22:7:36:18:7:2, adding water to obtain a uniformly mixed slurry with a water content of 8wt%, and then granulating it with a granulator; S3. The granules obtained after granulation are first kept at 150°C for 2 h, then at 450°C for 3 h, then at 1000°C for 1 h, and finally naturally cured.

[0028] Comparative Example 1: The difference from Example 1 is that no metal salt is added to S1.

[0029] Comparative Example 2: The difference from Example 1 is that in S1, water is replaced by an ammonia solution.

[0030] Comparative Example 3: The difference from Example 1 is that no fiber is added to S2.

[0031] Comparative Example 4: The difference from Example 1 is that no steel slag is added to S2.

[0032] Comparative Example 5: The difference from Example 1 is that S3 is only kept at 1000°C for 1 h.

[0033] The performance of the materials obtained in the above-mentioned Examples 1-3 and Comparative Examples 1-5 was tested, wherein the compressive strength was obtained by testing with a universal material testing machine, the specific surface area was obtained by nitrogen adsorption and desorption experiments, the carbon dioxide and hydrogen sulfide removal rates were obtained by placing the materials in a closed container containing carbon dioxide gas or hydrogen sulfide gas, and detecting the concentration changes of carbon dioxide gas or hydrogen sulfide gas over time by gas chromatography, and the antibacterial rate was tested by ASTM E2149-13a standard, and the results are shown in Table 1 below:

[0034] It can be concluded from Table 1 that the modified sludge dry powder, steel slag and fiber have high compressive strength, large specific surface area, excellent desulfurization and decarbonization ability and antibacterial properties through the calcination process. The lack of any of the above components or links will reduce their performance. In Comparative Example 1, due to the lack of metal salts, it cannot form a porous structure with sludge dry powder, and its performance has declined, especially the specific surface area and desulfurization and decarbonization ability have declined significantly. In Comparative Example 2, since the solvent was replaced with ammonia water, its microstructure and redox ability changed, and the performance declined accordingly. In Comparative Example 3, due to the absence of fiber as a reinforcing phase, its compressive performance decreased significantly. In Comparative Example 4, steel slag not only acts as a reinforcing phase but also desulfurizes and decarbonizes, and the compressive performance and desulfurization and decarbonization ability are significantly reduced without the addition of steel slag. In Comparative Example 5, only 1000℃ insulation for 1 h will cause the pore structure of the material to collapse, and its performance will decline accordingly.

[0035] The filling material proposed in the present invention can be injected into the well with the drilling fluid or fracturing fluid during drilling or fracturing to fill the pores in the rock or form a protective layer to prevent the intrusion of mud and sand. In the process of natural gas production, the components CO2 or H2S in the natural gas will be absorbed and fixed by the filling material. Among them, the metal salt can form a porous metal oxide material, so that the filling material has a 500 m 2 / g or more specific surface area, can adsorb carbon dioxide and hydrogen sulfide. In addition, the sulfate-reducing bacteria (producing hydrogen sulfide) and iron bacteria in the well can achieve sterilization function by forming strong oxidizing groups through the catalytic oxidation of the material of the present invention, thereby avoiding the reproduction of microorganisms in the well to produce carbon dioxide and hydrogen sulfide. CaO in lime, steel slag and lithium slag can absorb CO2 to form CaCO3, fix carbon dioxide, and other metal oxides in steel slag and lithium slag also absorb or adsorb carbon dioxide, and can be used as a skeleton material to provide mechanical strength. Fibers are used to enhance the mechanical strength of the filling material. That is, the resource utilization of dry powder after sludge incineration treatment is realized, the process flow is reduced, the treatment cost is reduced, and the economic value of sludge is improved; in summary, the material of the present invention removes carbon dioxide and hydrogen sulfide in the well, reduces the desulfurization and decarbonization process, and improves the economy; sterilizes and inhibits bacteria in the well to avoid the reproduction of microorganisms to produce carbon dioxide and hydrogen sulfide.

[0036] In the description of this specification, specific features, structures, materials or characteristics may be combined in an appropriate manner in any one or more embodiments or examples.

[0037] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a sludge dry powder-based filling material capable of purifying gas, characterized in that: The following steps are involved: A. Mixing sludge dry powder, metal salt, alkali and solvent into a solution, stirring to react, and drying to obtain modified sludge dry powder; B. Evenly mix the sludge dry powder modified in step A, lime, steel slag, lithium slag, cement, fiber and water to obtain a mixture, granulate, sinter and naturally cure the mixture to finally obtain a filling material.

2. The preparation method according to claim 1, characterized in that: In step A, the solid content of the solution is 30-50 wt %.

3. The preparation method according to claim 1, characterized in that: In step A, the mass ratio of the sludge dry powder, the metal salt and the alkali is 8:1:

1.

4. The preparation method according to claim 1 or 3, characterized in that: In step A, the metal salt includes at least two of iron nitrate, magnesium nitrate, aluminum nitrate, nickel nitrate, cerium nitrate, copper nitrate, zinc nitrate, manganese nitrate and cobalt nitrate.

5. The preparation method according to claim 1 or 3, characterized in that: In step A, the base is sodium hydroxide or urea.

6. The preparation method according to claim 1, characterized in that: In step A, the solvent includes at least one of water, ethanol, propanol, ethylene glycol, propylene glycol and butylene glycol.

7. The preparation method according to claim 1, characterized in that: In step A, the stirring reaction temperature is 80-150°C, the time is 2-24 h, and the drying temperature is 50-150°C.

8. The preparation method according to claim 1, characterized in that: In step B, the mass ratio of the sludge dry powder, lime, steel slag, lithium slag, cement and fiber is (20-30): (5-10): (30-40): (10-20): (3-10): (1-5), and the water content of the mixture is 5-10wt%.

9. The preparation method according to claim 1 or 8, characterized in that: In step B, the fiber includes at least one of bamboo charcoal fiber, basalt fiber, polyacrylamide fiber, carbon fiber and gypsum fiber; In step B, the sintering is a three-stage sintering, the first stage is kept at 100-200°C for 1-10 h, the second stage is kept at 400-600°C for 1-10 h, and the third stage is kept at 900-1100°C for 1-10 h.

10. Use of a filling material obtained by the preparation method according to any one of claims 1 to 9 in desulfurization and decarbonization in oil and gas wells.

Citation Information

Patent Citations

  • Industrial production method and system of sludge steam-pressing brick

    CN109912289A

  • Soil solidification material based on solid waste and biological enzyme and preparation method of soil solidification material

    CN113666705A

  • Method for controlling alkaline release and resource utilization of steel slag by using sludge biochar as well as product and application thereof

    CN116693141A

  • Method for preparing integral ozone catalyst by using sludge dry powder as raw material and application of integral ozone catalyst

    CN118594524A

  • Solid waste-based modified concrete and preparation method thereof

    CN118702454A